Proteostasis unbalance in prion diseases: Mechanisms of neurodegeneration and therapeutic targets - Thellung, Stefano; Corsaro, Alessandro; Dellacasagrande, Irene; Nizzari, Mario; Zambito, Martina; Florio, Tullio (Frontiers in Neuroscience, 2022)
Transmissible spongiform encephalopathies (TSEs), or prion diseases, are progressive neurodegenerative disorders of the central nervous system that affect humans and animals as sporadic, inherited, and infectious forms. Similarly to Alzheimer's disease and other neurodegenerative disorders, any attempt to reduce TSEs' lethality or increase the life expectancy of affected individuals has been unsuccessful. Typically, the onset of symptoms anticipates the fatal outcome of less than 1 year, although it is believed to be the consequence of a decades-long process of neuronal death. The duration of the symptoms-free period represents by itself a major obstacle to carry out effective neuroprotective therapies. Prions, the infectious entities of TSEs, are composed of a protease-resistant protein named prion protein scrapie (PrPSc) from the prototypical TSE form that afflicts ovines. PrPSc misfolding from its physiological counterpart, cellular prion protein (PrPC), is the unifying pathogenic trait of all TSEs. PrPSc is resistant to intracellular turnover and undergoes amyloid-like fibrillation passing through the formation of soluble dimers and oligomers, which are likely the effective neurotoxic entities. The failure of PrPSc removal is a key pathogenic event that defines TSEs as proteopathies, likewise other neurodegenerative disorders, including Alzheimer's, Parkinson's, and Huntington's disease, characterized by alteration of proteostasis. Under physiological conditions, protein quality control, led by the ubiquitin-proteasome system, and macroautophagy clears cytoplasm from improperly folded, redundant, or aggregation-prone proteins. There is evidence that both of these crucial homeostatic pathways are impaired during the development of TSEs, although it is still unclear whether proteostasis alteration facilitates prion protein misfolding or, rather, PrPSc protease resistance hampers cytoplasmic protein quality control. This review is aimed to critically analyze the most recent advancements in the cause-effect correlation between PrPC misfolding and proteostasis alterations and to discuss the possibility that pharmacological restoring of ubiquitin-proteasomal competence and stimulation of autophagy could reduce the intracellular burden of PrPSc and ameliorate the severity of prion-associated neurodegeneration.